Models for Foresight Use in International Development - Rhydderch, Alun (IDS Bulletin, 2016)
This article sets out the components of the foresight approach that ha s been adopted by many governments in the developed world, and identif ies elements of this 'dominant' approach that may hinder its uptake in developing countries. Instead, it suggests that a less rigid, more ex ploratory and normative approach may be better suited to many developi ng country contexts. With reference to the writings and practice of th e creator of 'la prospective', Gaston Berger, it argues for an attitud e that combines bold and inclusive thinking about how to create better futures with the pragmatic engagement with political and administrati ve systems that can help bring these about.